REVIEW OF FINANCIAL MANAGEMENT IN SUPPORTING VILLAGE FUND POLICIES TO IMPROVE VILLAGE DEVELOPMENT EFFECTIVENESS IN THE RIAU ARCHIPELAGO PROVINCE - Fanni Okan Perdana; Yeni Ardianti; Raja Afrikurniawan; Ade Rahmah; Zauwahir; Syahrianis; Muammar Khaddafi; Indrayani (Journal of Accounting Research, Utility Finance and Digital Assets, 2023)
In increasing the effectiveness of village development, policies on the use of village funds are needed in order to create strong, advanced, independent and democratic villages. Then the management of village financial management is the main factor for supporting fund policies based on the Regulation of the Minister of Home Affairs No. 20 of 2018 as a reference in financial management by the village government in the Village Revenue and Expenditure Budget funds, which is a form of management of village finance to carry out openly and responsibly for the prosperity of the village community, but in the implementation of village development sourced from the State Revenue and Expenditure Budget funds are still not optimal in accordance with management functions. therefore, this journal conducts a review of financial management carried out by village government officials as executors in managing village funds through a qualitative descriptive method based on secondary data. So that the results of this study identify that in implementing village fund financial management, village government officials are needed who have qualities that are able to be transparent, accountable, participatory, and orderly as well as disciplined in managing the budget so that the purpose of village funds can be realized to be development in a fair and equitable manner.